2012
DOI: 10.1038/oby.2012.6
|View full text |Cite
|
Sign up to set email alerts
|

Fermentable Carbohydrate Alters Hypothalamic Neuronal Activity and Protects Against the Obesogenic Environment

Abstract: Obesity has become a major global health problem. Recently, attention has focused on the benefits of fermentable carbohydrates on modulating metabolism. Here, we take a system approach to investigate the physiological effects of supplementation with oligofructose‐enriched inulin (In). We hypothesize that supplementation with this fermentable carbohydrate will not only lead to changes in body weight and composition, but also to modulation in neuronal activation in the hypothalamus. Male C57BL/6 mice were mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 38 publications
3
75
1
Order By: Relevance
“…The effects of microbiota and SCFAs on appetite regulation were investigated in a study comparing mice fed a high-fat diet supplemented with highly fermentable oligofructoseenriched inulin to supplementation with corn starch [64]. Inulin supplementation led to increased colonic SCFAs, decreased energy intake and adiposity, and increased neuronal activation within the ARC, suggesting a decrease in appetite.…”
Section: Appetite Regulationmentioning
confidence: 99%
“…The effects of microbiota and SCFAs on appetite regulation were investigated in a study comparing mice fed a high-fat diet supplemented with highly fermentable oligofructoseenriched inulin to supplementation with corn starch [64]. Inulin supplementation led to increased colonic SCFAs, decreased energy intake and adiposity, and increased neuronal activation within the ARC, suggesting a decrease in appetite.…”
Section: Appetite Regulationmentioning
confidence: 99%
“…NAFLD is commonly associated with an increased risk of developing Type 2 diabetes. Positive physiological effects have been linked with the production of short chain fatty acids (SCFA) by colonic fermentation of non-digestible carbohydrate (NDC), including reductions in hepatic fat content (2) . We have developed a novel inulin-propionate ester, whereby the SCFA propionate is bound to the NDC inulin.…”
mentioning
confidence: 99%
“…Analysis of the faecal samples found metabolic changes similar to those found in obese human subjects, including an increase in branched-chain fatty acid production (71) . Furthermore, evidence that fermentable NDC improve weight management in rodents and human subjects provides further support that compositional changes in the gut microbiota may contribute to the development of obesity (64,66,(72)(73)(74)(75)(76)(77) .…”
Section: Gut Microbiota In Lean V Obese Individualsmentioning
confidence: 99%
“…A number of rodent studies have observed reductions in bodyweight and adiposity following long-term consumption of fructans (66,72) . In a recent study, oligofructose, with or without probiotic Bifidobacterium animalis, was given to adult diet-induced obese Sprague-Dawley rats (73) .…”
Section: Anti-obesogenic Properties Of Non-digestible Carbohydratesmentioning
confidence: 99%
See 1 more Smart Citation